2021
DOI: 10.1093/nar/gkab850
|View full text |Cite
|
Sign up to set email alerts
|

COVID19db: a comprehensive database platform to discover potential drugs and targets of COVID-19 at whole transcriptomic scale

Abstract: Many open access transcriptomic data of coronavirus disease 2019 (COVID-19) were generated, they have great heterogeneity and are difficult to analyze. To utilize these invaluable data for better understanding of COVID-19, additional software should be developed. Especially for researchers without bioinformatic skills, a user-friendly platform is mandatory. We developed the COVID19db platform (http://hpcc.siat.ac.cn/covid19db & http://www.biomedical-web.com/covid19db) that provides 39 930 drug–target–pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Elsewhere the Ensembl COVID-19 resource ( 5 ) places the SARS-CoV-2 genome in the familiar Ensembl framework, providing evolutionary insights and integrating information regarding non-coding RNA structures (from Rfam ( 6 )) and variants. Other COVID-19 databases cover transcriptomics of infected cells, both in SCovid ( 7 ) from a single cell perspective that allows a tissue-specific view of infection and in COVID19db ( 8 ) with an emphasis on network analysis and opportunities for drug discovery. The final three databases consider the immune response to infection and the potential impact of viral genomic variants on its effectiveness.…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…Elsewhere the Ensembl COVID-19 resource ( 5 ) places the SARS-CoV-2 genome in the familiar Ensembl framework, providing evolutionary insights and integrating information regarding non-coding RNA structures (from Rfam ( 6 )) and variants. Other COVID-19 databases cover transcriptomics of infected cells, both in SCovid ( 7 ) from a single cell perspective that allows a tissue-specific view of infection and in COVID19db ( 8 ) with an emphasis on network analysis and opportunities for drug discovery. The final three databases consider the immune response to infection and the potential impact of viral genomic variants on its effectiveness.…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…4 b). To assess the association between methylation and expression of the genes in this gene set, we first compared their expression levels between COVID-19 patients (n=62) and healthy blood samples (n=24) [48] . This analysis showed that nine of the genes including MX1 , CMPK2 , PARP9 , TRIM22 , AIM2 , IFI44L , IFIT3 , IRF7, and EPSTI1 were significantly upregulated in blood of COVID-19 patients (p ≤ 0.05, ANOVA; |log 2 (FC)| ≥ 1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several user-defined rules (e.g., Lipinski’s rule of five, synthetic accessibility) are also introduced for filtering out undesired hits. (6) COVID19 db ( http://hpcc.siat.ac.cn/covid19db or http://www.biomedicalweb.com/covid19db ) is a user-friendly and open-access platform that integrates 95 COVID-19-related human transcriptomic datasets of 4,127 human samples across 13 body sites associated with exposure to 33 microbes and 33 drugs/agents in GEO and 39, 930 drug–target–pathway interactions among 2,037 drugs, 1,116 targets, and 207 pathways in DrugCentral and KEGG ( Zhang et al, 2022 ). In addition, 14 different analytical applications (included in the differential expression and coexpression modules) and a web service tool are designed and integrated to analyse the integrated data or the obtained human transcriptomic data.…”
Section: Targets For Novel Drug Developmentmentioning
confidence: 99%
“…(3) CovidExpress (https://stjudecab.github.io/covidexpress) is an open-access database and interactive visualization tool for intuitive investigation of SARS-CoV-2-related transcriptomes, and we collected approximately 1,500 human bulk RNA-seq datasets from publicly available resources (Djekidel et al, 2021) (Zhang et al, 2022). In addition, 14 different analytical applications (included in the differential expression and coexpression modules) and a web service tool are designed and integrated to analyse the integrated data or the obtained human transcriptomic data.…”
Section: Computational Tools Developed For Covid-19 Treatmentmentioning
confidence: 99%